Hemodynamic effects of chest compression interruptions during pediatric in-hospital cardiopulmonary resuscitation. (June 2019) - Morgan, Ryan W.; Landis, William P.; Marquez, Alexandra; Graham, Kathryn; Roberts, Anna L.; Lauridsen, Kasper G.; Wolfe, Heather A.; Nadkarni, Vinay M.; Topjian, Alexis A.; Berg, Robert A.; Kilbaugh, Todd J.; Sutton, Robert M.
Abstract: Aim: Animal studies have established deleterious hemodynamic effects of interrupting chest compressions. The objective of this study was to evaluate the effect of interruptions on invasively measured blood pressures (BPs) during pediatric in-hospital cardiac arrest (IHCA). Methods: This was a single-center, observational study of pediatric (<18 years) intensive care unit IHCAs in patients with invasive arterial catheters in place. Interruptions were defined as ≥1 s between chest compressions. Diastolic BP (DBP) and systolic BP (SBP) were determined for individual compressions. For the primary analysis, the average DBP and SBP of the 20 compressions preceding each interruption were compared to the average DBP and SBP of the first 20 compressions following each interruption utilizing non-parametric paired analyses. Linear regression evaluated the change in DBP during interruptions and following interruptions. Results: Thirty-two IHCA events met inclusion criteria, yielding 161 evaluable interruptions. The median age was 2.1 years. Return of circulation was achieved in 24 (75%). The median interruption duration was 2.4 [1.4, 7.0] seconds. Most patients were intubated pre-arrest and received epinephrine during CPR. BPs were not different pre- vs. post-interruption (DBP: 28.7 [21.6, 38.2] vs. 28.3 [21.0, 37.4] mmHg, p = 0.81; SBP: 82.0 [51.7, 116.7] vs. 85.4 [55.7, 122.2] mmHg, p = 0.07). DBP decreased 8.41 ± 0.73 mmHg (p < 0.001) during the first second of interruptions and 0.19 ± 0.02 mmHg/s (p < 0.001) in subsequent seconds. Conclusions: BPs following chest compression interruptions did not differ from pre-interruption BPs. These findings suggest that in the setting of high-quality in-hospital CPR, brief chest compression interruptions do not have persistent detrimental hemodynamic impact.